MICROBIOLOGICAL PROPERTIES OF BEEF IN VARIOUS MEAT SHOPS AT SEMARANG, INDONESIA - Nurwantoro, N.; Bintoro, V.P.; Legowo, A.M.; Purnomoadi, A. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
The aim of the study was to assess microbiological properties of beef sold in various meatshops in Semarang. There are five Indonesian goverment standard requirements to maintain the qualityof beef sold in Indonesia markets, as follows: (1) total plate count (TPC) for a maximum of 106 CFU/g,(2) total coliform bacteria for a maximum of 102 CFU/g, (3) total Escherichia coli up to 10 CFU/g, (4)total Staphylococcus aureus for a maximum of 102 CFU/g and (5) negative for Salmonella per 25 gsamples (SNI 3932, 2008). Beef samples were randomly taken from several traditional markets, meatshops and supermarkets. The result showed that all samples did not contain Salmonella but still couldnot meet one or some of the Indonesian government standard regulation. In conclusion, beef samplesgathered from some of the markets, generaly could not meet one or some of the five strictlyrequirements of the bacteriological properties.